Tracing Some Challenges of Higher Education Historically in Nepal through Tribhuvan University - Karna, Manoj Kumar (Historical Journal, 2024)
Tribhuvan University (TU) is the oldest and only central university in Nepal. It set a historical record in 2023 by convocating more than twelve thousand students at one time. Despite the presence of many regional and technical institutes and universities that contribute to Nepali society in higher education, Nepali students often prefer to study abroad after completing their school-level certificates. This trend has compelled Nepali university planners, educators, political parties, and governments to review the reasons for the brain drain among youth. The article aims to restore faith among Nepali citizens in the higher educational institutions available in the country, especially TU, and to encourage stakeholders to recognize the sensitivity of the issue so that brain drain can be reduced. To achieve this, the author selects various media writings on the higher education sector, websites, reports, and books on Gagne’s psychological theory and the history of higher education in Nepal, adhering to qualitative research methods. The findings indicate that there is a need for correction and self-evaluation among TU authorities, Nepali political parties, and other stakeholders to contribute positively and help the university maintain its good image.